2014
DOI: 10.1007/s12928-014-0267-3
|View full text |Cite
|
Sign up to set email alerts
|

A case of repeated occlusion in the common iliac artery due to an unexpected stent deformation

Abstract: We report a case experiencing repeated common iliac artery (CIA) occlusion due to an unexpected stent deformation. A 74-year-old man with intermittent claudication had undergone balloon-expandable stenting for the left CIA. Six years after his first stent implantation, his left CIA was totally occluded inside the stent. We performed revascularization for the left CIA and achieved sufficient balloon inflation and balloon-expandable stenting. Then, one and a half years later, his left CIA was re-occluded. CT ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Therefore, the specific characteristics of each patient and the specific care required should be considered before stent implantation. 10 Abdominal massage for spinal paraplegic patients should be recognized as a potential cause of stent failure and should be considered during optimal stent selection, with modification of the abdominal massage routine to avoid this complication in this population. Therefore, if balloon expandable stents are required, such as in our patient, we would suggest ensuring that the patient performs the intestinal evacuation correctly.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the specific characteristics of each patient and the specific care required should be considered before stent implantation. 10 Abdominal massage for spinal paraplegic patients should be recognized as a potential cause of stent failure and should be considered during optimal stent selection, with modification of the abdominal massage routine to avoid this complication in this population. Therefore, if balloon expandable stents are required, such as in our patient, we would suggest ensuring that the patient performs the intestinal evacuation correctly.…”
Section: Discussionmentioning
confidence: 99%
“…Balloon-expandable stents are vulnerable to deformation from external forces after in vivo deployment, as well to intra- 5 and postprocedural events 2,3 that subject the stent to extrinsic forces. In vitro testing has shown that the force required to deform different stents used for target vessels during FEVAR varies significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Most operators now use covered balloon-expandable stents, although previously uncovered stents were also used. 1 Balloon-expandable stents are vulnerable to deformation from external forces, and deformations have been reported at various sites in the body, including the common iliac 2 and carotid 3 arteries. Target vessel stent deformation and angulation after FEVAR is thought to be due to migration of the stent-graft.…”
Section: Introductionmentioning
confidence: 99%
“…Within each species, there are also differences between strains. In mice, for example, there are interstrain differences in the development of diet-induced NAFLD between C57BL/6, BALB/c, and C3H/HeN mice [39,40]. There are gender-specific differences too, for example, in the development of steatosis in rats [41].…”
Section: Animal Models In Liver Diseasementioning
confidence: 99%